Олександр Коваленко: штрихи до історичного портрета - Іванущенко, Г.М. (Сумський історико-архівний журнал, 2010)
Висвітлена біографія відомого громадського діяча, революціонера і вченого
Олександра Коваленка. Розкрита його роль в діяльності Харківської “Громади”, заснуванні
Революційної Української партії (РУП), повстанні на броненосці “Потьомкін”,
революційних подіях 1917-1920 рр. Розповідається про дипломатичну та науково-
педагогічну працю математика. Освещена биография известного общественного деятеля, революционера и
ученого Александра Коваленко. Раскрыта его роль в деятельности Харьковской
“Громады”, образовании Революционной Украинской партии (РУП), восстании на
броненосце “Потемкин”, революционных событиях 1917-1920 гг. Рассказывается о
дипломатической и научно-педагогической работе математика. The article pours the light on the biography of a famous public figure, revolutionist
and scientist Alexander Kovalenko. Much attention is paid to his role in organizing Kharkiv
“Hromada” activities, creating Revolutionary Ukrainian party (RUP), taking part in the
uprising onboard “Potemkin” ironclad and revolutionary events in 1917-1920. The great
mathematician’s diplomatic, scientific and pedagogical work is also depicted in the article.